2018
DOI: 10.3390/ma11091562
|View full text |Cite
|
Sign up to set email alerts
|

Selective Oxidation of Hydrogen Sulfide to Sulfur Using Vanadium Oxide Supported on Porous Clay Heterostructures (PCHs) Formed by Pillars Silica, Silica-Zirconia or Silica-Titania

Abstract: Vanadium oxide (V2O5) species has been supported on different porous clay heterostructures (with silica pillars, silica-zirconia with a molar ratio Si/Zr = 5 and silica-titania with a molar ratio Si/Ti = 5) by wetness incipient method. All catalysts were characterized by X-ray diffraction (XRD), N2 adsorption-desorption at −196 °C, NH3 thermoprogrammed desorption (NH3-TPD), Raman spectroscopy, diffuse reflectance UV-Vis and X-ray photoelectron spectroscopy (XPS). After that, the catalytic activity of the vanad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Soriano et al, [28] J.A. Cecilia et al [29] and by J.P. Holgado et al [30] and R. Nilsson et al, [31] can be observed. The peak at 2Θ = 27.7°could also be attributed to VO 2 (0 1 0) plane according to JCPDF file PDF 04-003-2035.…”
Section: Textural and Structural Characterizationmentioning
confidence: 92%
“…Soriano et al, [28] J.A. Cecilia et al [29] and by J.P. Holgado et al [30] and R. Nilsson et al, [31] can be observed. The peak at 2Θ = 27.7°could also be attributed to VO 2 (0 1 0) plane according to JCPDF file PDF 04-003-2035.…”
Section: Textural and Structural Characterizationmentioning
confidence: 92%
“…Furthermore, they found that the reduced V species were related with a low selectivity to SO 2 . Following a similar approach, other groups investigated the use of supported catalysts, such as VOx/TiO 2 [74], VOx/CeO 2 [75,76], and VOx/SiO 2 [77], and of vanadium oxides bronzes [78], which were the mechanism they found to be quite similar to the one already described and demonstrated by López-Nieto's group, with the oxidation and subsequent regeneration of the vanadium active phases, from V 5+ to V 4+ under reaction conditions.…”
Section: Removal Of H 2 Smentioning
confidence: 99%
“…Coal is one of the most sufficient fossil energy resources with inexpensive cost, and the consumption of coal has accounted for over 20% of consumed fossil fuels in the world [1,2]. Integrated gasification combined cycle (IGCC) power-plant is one of the strategies for efficient utilization of the coal.…”
Section: Introductionmentioning
confidence: 99%